Duellman, W. E. & Chaparro, J. C. (2008) Two distinctive new species of Pristimantis (Anura: Strabomantidae) from the Cordillera Oriental with a distributional synopsis of strabomantids in Central Peru. Zootaxa, 1918, 12–25. - Duellman, W. E.; Chaparro, J. C. (Zootaxa, 2008)
(Erratum)